Safety and efficacy of clonazepam in the treatment of juvenile myoclonic epilepsy: A meta-analysis - Faisal Al-Otaibi (Wolters Kluwer Medknow Publications, 2022)
Background: Juvenile myoclonic epilepsy (JME) is referred to as one of the most common epileptic syndromes. Several anti-epilepsy drugs (AEDs) have been developed and remain part of clinical intervention with varying safety and efficacy profiles. Comprehensive synthesis of the scientific evidence examining the safety and efficacy of clonazepam toward the treatment of JME was carried out in the study. Methods: A detailed scientific literature search was made utilizing the most relevant scientific studies published to date on the intervention of clonazepam in the management of JME. In this study, a detailed search was made in multiple databases, including PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), and Scielo databases. Confidence intervals among the studies and continuous measures, proportion, and risk factor analysis were determined using the MedCalC tool (Version 20.110) as per PRISMA guidelines. Results: A total of 6 studies out of 70 were found eligible for meta-analysis, where 186 JME patients were subjected to clonazepam intervention with controls. Clonazepam was reported effective in comparative analysis among six studies where P < 0.001. The result also shows a higher prevalence of JME in the female population compared to males (male versus female; 86/110). Efficacy and safety of clonazepam were reported significant as well. Conclusion: Clonazepam is effective AEDs for the management of JME. However, more clinical evidence requires for statistical validation of clinical efficacy.